„Der Seherin Gesicht“. Nordische Weissagungen in der bildenden Kunst des 18. und 19. Jahrhunderts - Timme, Sarah (IKON, 2013)
Abstract Der Aufsatz untersucht die Ikonographie nordisch-germanischer Seherinnen. In mehreren mittelalterlichen islandischen Texten treten sog. Volven auf, Seherinnen oder Prophetinnen, die mythologische Stoffe erzahlen. Als die nordischen Mythen in der zweiten Halfte des 18. Jahrhunderts im Kontext der Asthetik des Erhabenen das Interesse einiger bildender Kunstler weckten, waren es diese Figuren, die zuerst dargestellt wurden. Die Transformation des literarischen Genres der Weissagung in Bilder losten die Kunstler auf verschiedene Weise. Im 19. Jahrhundert hatte sich dann die Ikonographie der Volva herausgebildet, die sich sowohl an Ubersetzungen altnordischer Texte als auch an der christlichen und antiken Ikonographie orientierte. Abstract So-called volur (sing. volva; seeresses or prophetesses) can be found in a number of medieval Icelandic texts, in which mythological tales are told. When Norse myths began to become popular among artists in the second half of the eighteenth century, these figures were the first to be depicted. This interest was kindled by Thomas Gray, who published an English translation of the eddic lay Baldrs draumar (Baldr’s Dreams) under the title The Descent of Odin (1762), in which a volva appears. Many artists struggled to transform the figure of the volva from the textual to the visual medium, as can be seen in the drawings of Henry Fuseli (Johann Heinrich Fussli). In the period around the year 1800, it was common for artists to represent volur as speaking figures wearing long flowing robes. Other volur attributes found in art history include veils and naked breasts. The latter is especially true for representations of Velleda, a Germanic seeress who was a subject in Tacitus’ writings as well as many artistic renderings in France. Other attributes of seeresses, such as a rod, can be traced back to Old Norse sources. In addition to Velleda and the prophetess from Baldrs draumar - on which Richard Wagner’s Erda is based in The Ring of the Nibelung and who also became a pictorial motif for several of Wagner’s followers in the last quarter of the nineteenth century - the seeress who prophesies the fate of the Norse gods in Voluspa (The Prophecy of the Seeress) has also been portrayed in a great number of paintings. In book illustrations, volur are also preferred figures in the frontispiece, thereby functioning as pictorial narrators of the succeeding texts (quite often translations of the Poetic Edda). Abstract Takozvane volur (jd. volva; svećenica ili proročica) mogu se naći u mnoštvu srednjovjekovnih islandskih tekstova u kojima se prepričavaju mitološke priče. Popularizacijom skandinavskih mitova među umjetnicima druge polovine 18. stoljeća upravo su ovi likovi bili prvi koje se prikazivalo. Interes je za njima pobudio Thomas Gray izdavanjem engleskog prijevoda epa Baldrs draumar (Baldrov san), pod naslovom Odinov silazak (1762.), u kojem se pojavljuje volva. Kao što se može vidjeti u crtežima Henryja Fuselia (Johann Heinrich Fussli), mnogi su se umjetnici borili s transpozicijom volvae iz tekstualnog u slikarski prikaz. U razdoblju oko 1800. godine umjetnici su često prikazivali volur kao likove koji govore, odjevene u dugu, lepršavu draperiju. Ostali atributi volura u povijesti umjetnosti uključuju velove i gola prsa. Potonji je karakterističan za prikaze Vellede, germanske svećenice koja se pojavljuje kao lik u Tacitovim djelima i u mnogim francuskim umjetničkim interpretacijama. Podrijetlo ostalih atributa svećenica, primjerice štap, može se pratiti do staronordijskih izvora. Uz Velledu i proročicu Baldrovog sna (na čijem se liku zasniva Wagnerova Erda iz Prstena Nibelunga, koja postaje i slikarski motiv nekolicine Wagnerovih sljedbenika zadnje četvrtine 19. stoljeća), svećenica koja proriče sudbinu nordijskih bogova u Voluspai (Proročanstvo svećenice) također je bila portretirana u nizu umjetničkih slika. U ilustracijama knjiga volur su, također, likovi koje se koristi na naslovnicama te pritom služe kao vizualni nagovjestitelji teksta - najčešće prijevoda Starije Edde.